2014
DOI: 10.3844/jcssp.2014.925.934
|View full text |Cite
|
Sign up to set email alerts
|

Content Based Batik Image Retrieval

Abstract: Content Based Batik Image Retrieval (CBBIR) is an area of research that focuses on image processing based on characteristic motifs of batik. Basically the image has a unique batik motif compared with other images. Its uniqueness lies in the characteristics possessed texture and shape, which has a unique and distinct characteristics compared with other image characteristics. To study this batik image must start from a preprocessing stage, in which all its color images must be removed with a grayscale process. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 8 publications
0
11
0
2
Order By: Relevance
“…Rangkuti et al [8] conducted research on content based batik image retrieval. The research is done using the features of texture by using wavelet and features shape by using moment invariant.…”
Section: Introductionmentioning
confidence: 99%
“…Rangkuti et al [8] conducted research on content based batik image retrieval. The research is done using the features of texture by using wavelet and features shape by using moment invariant.…”
Section: Introductionmentioning
confidence: 99%
“…This study applied edge feature orientation combined with micro structure descriptor for enhancing retrieval performance. Rangkuti, et al [10] reported using Canny edge detection to an input image, wavelets as texture features and invariant moment as shape features method. The performance results achieved optimal precision of average 90% -92%.…”
Section: Introductionmentioning
confidence: 99%
“…Basically, the depiction of the batik is a process of matching the characteristics of image search with characteristics (Rangkuti et al, 2014;and Hiremath & Pujari, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some support functions in the craft motifs on the shape and texture with any characteristic value generated through the process of wavelet decomposition, including the gain coefficient approximation. The image of batik craft fabrics includes: Motif; Color; Ornament; Decomposition pattern recognition; Edge Detection; Grayscale; Feature Extraction; and Texture (Rangkuti, Harjoko, & Putro, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%